DRUM LEARNING AND MOTOR SKILLS: EXPLORING TEACHER MOTIVATION AND DIRECT STRATEGIES IN PRIVATE LESSONS - Sembiring, Piter (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This study explores the integration of teacher motivation and direct instructional strategies in the development of students"™ motor skills during private drum lessons. The background highlights the pedagogical importance of drumming as both a musical and developmental tool. A descriptive qualitative approach was applied at two music institutions in Bandung, involving 15 elementary students through interviews, participatory observation, and documentation. The results reveal that intrinsic motivation such as personal satisfaction and emotional connection plays a pivotal role in enhancing teaching effectiveness. Teachers"™ use of structured demonstrations, kinesthetic explanations, and adaptive feedback significantly improved students"™ rhythmic coordination and neuromuscular awareness. Discussion emphasizes how direct instruction, when emotionally engaging and physically responsive, creates a holistic and immersive learning experience. The study concludes that music education should integrate psychological and biomechanical perspectives to optimize motor skill development. This finding has implications for teacher training programs aiming to foster interdisciplinary competencies in music pedagogy